KARAKTERISTIK FISIK TANAH PADA BERBAGAI KELERENGAN DAS POBOYA KOTA PALU - Kalembiro, Meliza; Rajamuddin, Ulfiyah A.; Zaenuddin, Rahmat (AGROTEKBIS, 2018)
This study aims to determine the physical properties of the soil at various slopes of  watershed Poboya Palu City so that it can be used as a reference / consideration in the management of the physical properties of the soil, so that the land can be properly utilized. This research is a descriptive exploratory approach of variables through field survey and supported the results of laboratory analysis of the soil in the Environment Faculty of Agriculture, University Tadulako. This research was conducted in June 2015 and September 2015. The results showed that the physical characteristics of the soil at various gradients of watershed Poboya highly variable, namely the soil texture is dominated by medium-sized particles with a class of argillaceous texture, permeability tend fast to very fast, very high porosity, soil bulk density is relatively modest, and the organic matter content is low to moderate. Based on the physical properties of soil slope changes the value of the texture in the form of sand, silt, and clay is low, increased permeability, increased porosity, bulk density decreases, and increased organic matter. Vertically, the physical characteristics of the soil changes according to the depth value, the texture in the form of sand, silt, and clay is low, permeability increased, decreased porosity, bulk density increased, and organic matter decline.